Low temperature physics without a cryostat: laser cooling and trapping of atoms - Bigelow, N. P. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 1998)
In recent years, there has been significant interest in the laser manipulation of neutral atoms, and specifically in the use of light fields to manipulate not only the internal but also the external coordinates of an atom. Among the most dramatic results of this work have been the production of dense ultra-cold samples of trapped neutral atoms. These samples have been used to expand the horizons of fundamental physics and have made possible significant advancements in metrology. Furthermore, the ability to manipulate atomic motion with light has helped to create entirely new fields of research such as atom optics where matter wave analogues of light wave systems are investigated and optical where light is used to create a periodic array of atoms similar to crystals.